CT predictors of post-procedural aortic regurgitation in patients referred for transcatheter aortic valve implantation: An analysis of 105 patients - Marwan, Mohamed; Achenbach, Stephan; Ensminger, Stefan M.; Pflederer, Tobias; Ropers, Dieter; Ludwig, Josef; Weyand, Michael; Daniel, Werner; Arnold, Martin (International Journal of Cardiovascular Imaging, 2013)
Cardiac computed tomography (CT) allows accurate and detailed analysis of the anatomy of the aortic root and valve, including quantification of calcium. We evaluated the correlation between different CT parameters and the degree of post-procedural aortic regurgitation (AR) after transcatheter aortic valve implantation (TAVI) using the balloon-expandable Edwards Sapien prosthesis. Preintervention contrast-enhanced dual source CT data sets of 105 consecutive patients (48 males, mean age 81 ± 6 years, mean logEuroSCORE 34 ± 13 %) with symptomatic severe aortic valve stenosis referred for TAVI using the Edwards Sapien prosthesis (Edwards lifesciences, Inc., CA, USA) were analysed. The degrees of aortic valve commissural calcification and annular calcification were visually assessed on a scale from 0 to 3. Furthermore, the degree of aortic valve calcification as quantified by the Agatston score, aortic annulus eccentricity, aortic diameter at the level of the sinus of valsalva and at the sinotubular junction were assessed. Early post-procedural AR was assessed using aortography. Significant AR was defined as angiographic AR of at least moderate degree (AR ≥ 2). Visual assessment of the degree of aortic annular calcification as well as the Agatston score of aortic valve calcium correlated weakly, yet significantly with the degree of post-procedural AR (r = 0.31 and 0.24, p = 0.001 and 0.013, respectively). Compared to patients with AR<2, patients with AR ≥ 2 showed more severe calcification of the aortic annulus (mean visual scores 1.9 ± 0.6 vs. 1.5 ± 0.6, p = 0.003) as well as higher aortic valve Agatston scores (1,517 ± 861 vs. 1,062 ± 688, p = 0.005). Visual score for commissural calcification did not differ significantly between both groups (mean scores 2.4 ± 0.5 vs. 2.5 ± 0.5, respectively, p = 0.117). No significant correlation was observed between the degree of AR and commissural calcification, aortic annulus eccentricity index or aortic diameters. The extent of aortic valve annular calcification, but not of commissural calcification, predicts significant post-procedural AR in patients referred for TAVI using the balloon-expandable Edwards Sapiens prosthesis.
CRIS-Team Scopus Importer:2023-03-08
Keywords: AR; CT; TAVI